Long and Short Terms Treatment Effect of Peganum harmala on Female Albino Rats Fertility and Pregnancy - A. EL-DWAIRI, QASIM (Asian Journal of Chemistry, 2010)
This study was conducted to investigate the effects of Peganum harmala oral administration on fertility and pregnancy outcome of female albino rats. Exposure to Peganum harmala for 4 weeks did not have significant effect on most parameters investigated. However, a slight decrease in the relative ovarian and embryo weights was observed. Administration of Peganum harmala for 12 weeks significantly reduced the percentage of pregnancies and the number of implantation sites when compared with controls. In addition, a decrease in ovarian weights and in viable fetuses' number was also observed.